Security+ guide to network security fundamentals - Ciampa, Mark (Course Technology, 2009)
This book was required for an online course and i found it to be very adequate and informative. if one does the exercises and labs that are associated with the book they can gain a valuable insight into the field of network technology and skills to protect themselves and their organizations.